Comparison between bipolar vessel sealer (LigaSure vessel sealer) and harmonic scalpel in total laparoscopic hysterectomy - Bansal, Vandana; Bansal, Arpit; Bansal, Ashwani Kumar; Kumar, Ajay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of the present study was to compare the use of bipolar Vessel Sealer with Harmonic Scalpel (HS) during total laparoscopic hysterectomy with respect to estimated blood loss and related postoperative complications. Methods: A retrospective study was conducted in the Jeevan Jyoti hospital and Guru Gobind Singh Memorial Vanadana Women’s hospital, Allahabad, U.P., India. Two forty two patients were enrolled who underwent total laparoscopic hysterectomy and were randomized into two homogenous groups: bipolar vessel sealer and harmonic scalpel. Results: Estimated blood loss was significantly less in bipolar vessel sealer when compared with harmonic scalpel. No significant difference was observed in postoperative complications. Conclusions: The bipolar vessel sealer is a reliable and safe tool for reducing intraoperative blood loss in patients undergoing total laparoscopic hysterectomy. More randomized studies need to be done to confirm the advantages of this technique.